General characteristics of Islamic philosophy of education: how it is relevant to society of globalizing world - Shogar, Ibrahim (2014)
The major aim of this paper is to highlight the general characteristics of Islamic philosophy of education. The basic assumption of the paper is that the Islamic philosophy of education is relevant to the needs of globalizing society, due to certain factors. For that purpose, the four basic educational questions on the recipient, the content, objectives, and the method are discussed. The major problem of Islamic education, according to the paper, is that there is lack of awareness on basic characteristics of Islamic educational philosophy; therefore, it was hard for Muslim intellectuals to deal properly with results of educational problems such as religious extremism and secularism in the Muslim communities; let alone to attract the attention of global community to the advantages of Islamic education system as an effect method to produce a balanced personality. For example, the steering committee of the First World Conference on Muslim Education, which held in Makkah in 1977, emphasizes that: It is strongly felt that it is necessary for the Muslims to have a truly Islamic education. And education can be truly Islamic only if Muslim scholars can produce Islamic concepts for all branches of human knowledge and Muslim countries disseminate these concepts among Muslim intellectuals and students by getting their mind purified of all non-Islamic ideas and by making them more and more conscious of the significance and utility of these concepts through research projects, textbooks and teacher training programmes (Proceedings of Makkah Conference, p 10) . More than four decades have passed since this statement was, but our students of the higher learning, especially in science and technology, are still depending only on textbooks which produced by others. So, the important question is what is the problem? This paper has attempted to answer this basic question.